2016
DOI: 10.1007/s11103-015-0421-z
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic analysis reveals LeACS-1 as a positive regulator of ethylene-induced shikonin biosynthesis in Lithospermum erythrorhizon hairy roots

Abstract: The phytohormone ethylene (ET) is a crucial signaling molecule that induces the biosynthesis of shikonin and its derivatives in Lithospermum erythrorhizon shoot cultures. However, the molecular mechanism and the positive regulators involved in this physiological process are largely unknown. In this study, the function of LeACS-1, a key gene encoding the 1-aminocyclopropane-1-carboxylic acid synthase for ET biosynthesis in L. erythrorhizon hairy roots, was characterized by using overexpression and RNA interfere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 63 publications
0
26
0
Order By: Relevance
“…This indicated that G10H and 12OPR unigenes should be up-expressed in all RR lines from above three Lithospermeae plants, and probably related to shikonin biosynthesis in this present study. Moreover, the functional validation of the G10H and 12OPR unigenes is now underway, according to the similar strategy as reported in our previous papers 14, 31, 32 .
Figure 6The qRT-PCR verification of the G10H and 12OPR unigenes’ expression profiles between GL and RR lines in Lithospermum erythrorhizon ( Le ), Arnebia euchroma ( Ae ) and Echium plantagineum ( Ep ). ( a ) G10H - LeCL2572 .
…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…This indicated that G10H and 12OPR unigenes should be up-expressed in all RR lines from above three Lithospermeae plants, and probably related to shikonin biosynthesis in this present study. Moreover, the functional validation of the G10H and 12OPR unigenes is now underway, according to the similar strategy as reported in our previous papers 14, 31, 32 .
Figure 6The qRT-PCR verification of the G10H and 12OPR unigenes’ expression profiles between GL and RR lines in Lithospermum erythrorhizon ( Le ), Arnebia euchroma ( Ae ) and Echium plantagineum ( Ep ). ( a ) G10H - LeCL2572 .
…”
Section: Resultsmentioning
confidence: 83%
“…euchroma and E . plantagineum were germinated according to the methods, as previously reported 14, 26 . The germinated seeds were then transferred into square plastic pots (50 * 30 * 30 cm) with peat growing medium (Pindstrup, Denmark) and were cultured in a greenhouse at 23 ± 1 °C under a 16 h/day photoperiod for approximately 60 to 90 days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The shikonin and its derivative content reached the highest level on day 6 (Fang et al . ). The expression level of LeMRP in hairy roots was determined through real‐time PCR to confirm the transgenic effects.…”
Section: Resultsmentioning
confidence: 97%